FACTORS AFFECTING THE QUALITY OF PICKLED LOTUS ROOT PRODUCTS IN GIANG THANH DISTRICT, KIEN GIANG PROVINCE - Huynh Van Quoc Canh; Le Bich Tuyen; Danh Trung Tinh; Tran Thi Tuyet Nhi (HUIT Journal of Science, 2026)
This study aimed to investigate factors influencing the quality of pickled lotus root products in Giang Thanh district, Kien Giang province, including temperature and blanching time prior to pickling; initial salt concentration in the fermentation liquid; fermentation temperature; initial density of Lactiplantibacillus plantarum bacteria. The results of the study showed that when blanching lotus roots at 80 oC for 30 seconds, the initial NaCl salt concentration was 4% and the fermentation temperature was 30 oC and the initial density of Lactiplantibacillus plantarum bacteria added to the fermentation liquid was 107 CFU/g, the product had good hardness and brightness, high acid content, pH met the standards of pickled vegetables and fruits, and the product had the best quality.